Mainstream Secondary Teachers' Perception Towards Social Media and YouTube in the Field of Special Education - Sgourelli Vasiliki; Triantafyllaki Angeliki (2017)
Introduction, Literature Review, Informal/ Formal and Self-Dircted vs Self-Regulated Learning, Beyond Teachers' Subject Knowledge, Current Learning Theories Related to Social Networked Communities, Building Resilience Through Facebookand YouTube, The Importance and Contribution of the Study, Methodology, Methodological Approach, Method of Data Collection, Research Design, Data Analysis, Using NVIVO, Pilot Study, Findings, Redefining Teachers' Role in a Digital Era, Isolation vs Social Media, Teachers' Resilience and Social Media, The Impact of SNS (Facebook and YouTube) and Future Implications, Teachers' and Students' Awareness and Motivation Through SNS on SEND Issues, Discussion, Redefining Teachers' Roles, Teachers Isolation vs Social Media, Coclusion, References, Appendices.